Diversity of water yam (Dioscorea alata L.) accessions from Cote d'Ivoire based on SNP markers and agronomic traits - Bakayoko, L.; Pokou, D.N.; Kouassi, A.B.; Agre, A.P.; Kouakou, A.M.; Dibi, K.E.B.; Nzue, B.; Mondo, J.; Adebola, P.O.; Akintayo, O.T.; Asfaw, A.; N'guetta, A.S. (MDPI, 2021)
Dioscorea alata (L.), also referred to as water, winged, or greater yam, is one of the most economically important staple food crops in tropical and subtropical areas. In Côte d’Ivoire, it represents, along with other yam species, the largest food crop and significantly contributes to food security. However, studies focusing on better understanding the structure and extent of genetic diversity among D. alata accessions, using molecular and phenotypic traits, are limited. This study was, therefore, conducted to assess the pattern of genetic variability in a set of 188 D. alata accessions from the National Agronomic Research Centre (CNRA) genebank using 11,722 SNP markers (generated by the Diversity Arrays Technology) and nine agronomic traits. Phylogenetic analyses using hierarchical clustering, admixture, kinship, and Discriminant analysis of principal component (DAPC) all assigned the accessions into four main clusters. Genetic diversity assessment using molecular-based SNP markers showed a high proportion of polymorphic SNPs (87.81%). The analysis of molecular variance (AMOVA) showed low molecular variability within genetic groups. In addition, the agronomic traits evaluated for two years in field conditions showed a high heritability and high variability among D. alata accessions. This study provides insights into the genetic diversity among accessions in the CNRA genebank and opens an avenue for sustainable resource management and the identification of promising parental clones for water yam breeding programs in Côte d’Ivoire.